2019
DOI: 10.24266/0738-2898-37.4.108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rosa Species Accessions for Resistance to Eriophyid Mites1

Abstract: Rose rosette disease, caused by rose rosette virus (RRV), is an epidemic affecting nearly every rose cultivar in the United States. The only hosts for Phyllocoptes fructiphilus, the eriophyid mite that vectors RRV, are Rosa species. Eighteen Rosa species were evaluated for mite resistance by collecting foliage samples from July to November in 2016 and 2017, from which mites were extracted. Mites were isolated through a series of sieves and counted using a stereomicroscope. The response variable was expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Counting eriophyid mites is a time-intensive process, particularly when processing large number of samples from heavily infested plants. The short life cycle (approximately 7 d) of eriophyids is conducive to rapid and large population increase, that compelled researchers to evaluate new methods for population estimation using standardized grids to count mites per unit (Fournier et al 2004, Chandrashekar et al 2020) or counting extracted mites in aliquots (Siriwardena et al 2005, Solo et al 2019. Furthermore, nondestructive methods with minimal damage to plants are convenient for monitoring mites in commercial production systems (Moerkens et al 2018) and research purposes (Sircom 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counting eriophyid mites is a time-intensive process, particularly when processing large number of samples from heavily infested plants. The short life cycle (approximately 7 d) of eriophyids is conducive to rapid and large population increase, that compelled researchers to evaluate new methods for population estimation using standardized grids to count mites per unit (Fournier et al 2004, Chandrashekar et al 2020) or counting extracted mites in aliquots (Siriwardena et al 2005, Solo et al 2019. Furthermore, nondestructive methods with minimal damage to plants are convenient for monitoring mites in commercial production systems (Moerkens et al 2018) and research purposes (Sircom 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For its presence-absence (binomial sampling, Hall et al 2007), direct counts using a hand lens are appropriate (Hoy 2011). However, to estimating populations, counting methods based on extraction techniques such as sticky tapes, leaf brushing, washing-and-sieving, and centrifugation are broadly accepted (Harvey and Martin 1988, Perez-Moreno and Moraza-Zorilla 1998, Davies et al 2002, Faraji et al 2004, Monfreda et al 2007, Shanini et al 2009, McCarren and Scott 2013, Solo et al 2019). Nonetheless, using such conventional approaches are inadequate for counting tiny mites such as Eriophyidae, especially from sticky hemp leaves with glandular hairs.…”
mentioning
confidence: 99%
“…Mite reproduction studies on 32 modern rose cultivars have shown that modern roses are good hosts for Pf [ 6 , 19 , 30 ], although additional work with greater genetic diversity of rose cultivars is necessary to assess the resistance of cultivated roses to the mite vector. In contrast, Pf was not able to reproduce on two rose species accessions ( R. bracteata and R. carolina ) or plants from related genera in the Rosaceae family.…”
Section: Introductionmentioning
confidence: 99%